Simulation and analysis of voice over internet protocol (VoIP) network using network simulator 2 / [compact disc] - 431329 Leong, Wei Kheng (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Electrical)) - Universiti Teknologi Malaysia, 2003